Iowa Birdline update, December 2, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for December 2, 1991. The highlights for the update include sightings of Thayer's Gulls, Lesser Black-backed Gull, both a Mute Swan and an immature Tundra Swan, White-winged Scoter and a Long-tailed Duck. Also included are handwritten notes with sightings of a Great Black-backed Gull and an immature Golden Eagle. Epson - sheet feed/flatbed